Determinants of Nurse Burnout Syndrome In Palembang City Hospital: A Cross-Sectional Study - Ismar Agustin; Ratna Ningsih; Imelda; Muliyadi; Azwaldi; Nathalia Ramadhanti (Sahabat Publikasi Kuu, 2023)
Nurses are at risk of experiencing various impacts due to work that affect their health. Nurses are at risk of experiencing mental health problems that can affect the quality of life and productivity of nurses, including burnout syndrome or mental fatigue. This study aims to identify the determinant factors associated with nurse burnout. This study used a cross-sectional design with 63 respondents using a purposive sampling method. Bivariate data analysis with chi square and multivariate with logistic regression. The results of the analysis show that most of the nurses experience burnout. Age, marital status and self-efficacy are significantly related to nurse burnout. Multivariate analysis showed self-efficacy (Exp(B) 0.029; 95% CI 0.004-0.197) as the most dominant factor causing nurse burnout. Nurses with low self-efficacy have a seven times higher risk of experiencing burnout than nurses who have high self-efficacy, but burnout is also influenced by other factors such as age and marital status. Future researchers are advised to consider other factors that can affect burnout so that they have different criteria and maximum research results